Modified TBL: Navigating Delirium in an Elderly Surgical Patient - Kathryn Denson; Travis Webb; John Petronovich; Thomas Wade; Diane Brown (Association of American Medical Colleges, 2015)
Abstract Introduction The geriatric population is the fastest growing demographic in healthcare, with the elderly population greater than 65 years of age projected to exceed 20% of the total US population by 2030. Geriatric-specific education is essential to ensure competency of surgical graduates to care for this population. However, competing educational demands in a constricted duty hours environment may combine to leave this educational gap unnoticed and unfilled. At the Medical College of Wisconsin, geriatricians and trauma surgeons worked together to create and implement a geriatrics education modified TBL curriculum for general surgery residents. Key curriculum content gaps (e.g., delirium, polypharmacy) were identified through a 24-question survey, with content identified through the Surgical Council on Resident Education curriculum and framed within the ACGME Competencies. Methods Curriculum content was delivered using a modified TBL approach. Residents self-assessed their competency level in both pre− and post-TBL curriculum intervention. Residents' presession work included reading of a delirium review article and reviewing a list of high-risk medications in geriatric patients. Class-session work included readiness assessment through individual and group assessment questions and then knowledge application exercises with structured debriefing/discussions using a geriatric surgical patient case. Relevance and need for curriculum topic gaps was determined through a Likert-style survey on geriatric training in general surgery sent to 40 general surgery residents and 65 surgery faculty. Results Thirty residents and 22 faculty completed the survey. Residents rated themselves as overall "competent in geriatric care" more frequently than the faculty rated them on all 16 ACGME Competency-related questions (p = .0002). While faculty perceived a greater need for improvement in training than did residents, both groups separately identified identical competency areas to target for improvement (delirium, high-risk medications). In postmodified TBL session evaluations (scale: 1 = poor, 7 = excellent), residents rated "Instructional strategies advanced my learning about geriatrics" as 6.2, "Overall content of the session" as 6.3, and "Overall effectiveness of today's session" as 6.4. Postmodified TBL session resident self-assessment (scale: 1 = strongly disagree, 4 = strongly agree) showed "Explain the science that underlies effective care of older adults" as 3.4, "Assess, diagnose and/or manage clinical conditions in older adults" as 3.5, and "Access and use evidence-based geriatrics specific resources/point of care tools" as 3.6. Discussion Providing geriatric-specific education is an increasingly important aspect of medical education given an aging population. This resource attempts to address this issue using a modified-TBL approach.